2000
DOI: 10.1159/000013556
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Macrophage Colony-Stimulating Factor as an Adjuvant to Hepatitis B Vaccination in Maintenance Hemodialysis Patients

Abstract: Patients on maintenance hemodialysis (HD) have poor seroconversion rate after hepatitis B vaccination. The present study was designed to test the efficacy of granulocyte-macrophage colony-stimulating factor (GM-CSF) as an adjuvant to hepatitis B vaccination for improving seroconversion rate in maintenance HD patients. Twelve chronic HD patients were randomly assigned to receive either hepatitis B vaccination alone or hepatitis B vaccination 24 h after 1 dose of GM-CSF for primary immunization. A group of 16 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
3
23
0
2
Order By: Relevance
“…These patients had significantly higher seroprotective titers compared with HBV vaccine alone (p < 0.05). 28 Similarly, in the booster group, GM-CSF adjuvant significantly increased the seroconversion rate (p < 0.02) and showed significantly higher mean anti-HBV titers than the HBV vaccine group (p < 0.05). 28 …”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 82%
See 2 more Smart Citations
“…These patients had significantly higher seroprotective titers compared with HBV vaccine alone (p < 0.05). 28 Similarly, in the booster group, GM-CSF adjuvant significantly increased the seroconversion rate (p < 0.02) and showed significantly higher mean anti-HBV titers than the HBV vaccine group (p < 0.05). 28 …”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 82%
“…22 Similarly, in patients with HIV or those on haemodialysis, GM-CSF as an adjuvant administered prior to a primary or booster HBV vaccine dose appears to facilitate greater immunological protection against HBV infection than HBV vaccine alone. 25,27,28 It should be noted that GM-CSF was administered prior to the vaccine, which could complicate compliance in routine immunizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous clinical studies attempted to use GM-CSF as a bolus injection to improve the efficacy of HBsAg vaccine in healthy nonresponders (22) and in hemodialysis patients (23)(24)(25)(26)(27)(28)(29). However, in general, the improvement in vaccine efficacy was not impressive, which might be due to the short serum half-life of GM-CSF (41) and the low local GM-CSF concentration at the point where the immune response was taking place.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, GM-CSF, in the form of a recombinant protein or a gene product encoded by plasmid DNA or viral vectors, has been codelivered as an adjuvant and has proved effective in enhancing immune responses to a number of vaccines (20,21). In terms of HBV vaccines, systemic administration of rGM-CSF was investigated as an adjuvant in healthy nonresponders (22) and in hemodialysis patients (23)(24)(25)(26)(27)(28)(29). However, in these studies, GM-CSF showed no effect or only moderately increased the seroconversion rate and anti-HBs titers.…”
mentioning
confidence: 99%